query19

#$&*

course MTH 173

8/7/113pm

019. `query 19

*********************************************

Question: `qQuery problem 3.4.27 was 3.4.29 (3d edition 3.4.20) was 4.4.12 Derivative of `sqrt(

(x^2*5^x)^3

What is the derivative of the given function?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

&&&&&&&&&&&&&&&&&&&&&&&&

************************

y = ((x^2*5^x)^.5)^3 = (x^2*5^x)^1.5

y' = 1.5((x^2*5^x)^.5)(2x(5^x) + x^2(ln(5))(5^x))

y' = 1.5sqrt(x^2*5^x)(5^x)(2x+ln(5)(x^2))

&&&&&&&&&&&&&&&&&&&&&&&&

************************

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** The function is `sqrt( (x^2 * 5^x)^3 ) = (x^2 * 5^x)^(3/2).

This is of form f(g(x)) with g(x) = x^2 * 5^x and f(z) = z^(3/2). Thus when you substitute you

get f(g(x)) = g(x)^(3/2) = (x^2 * 5^x)^(3/2).

(x^2 * 5^x) ' = (x^2)' * 5^x + x^2 * (5^x) ' =

2x * 5^x + x^2 ln 5 * 5^x =

(2x + x^2 ln 5) * 5^x.

`sqrt(z^3) = z^(3/2), so using w(x) = f(g(x)) with f(z) = z^(3/2) and g(x) = x^2 * 5^x we get

w ' = (2x + x^2 ln 5) * 5^x * [3/2 (x^2 * 5^x)^(1/2)] = 3/2 (2x + x^2 ln 5) * | x | * 5^(1/2 x).

Note that sqrt(x^2) is | x |, not just x, since the square root must be positive and x might not

be. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `qQuery problem 3.4.26 was 3.4.28 (3d edition 3.4.19) (was 4.4.20) derivative of 2^

(5t-1).

What is the derivative of the given function?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

&&&&&&&&&&&&&&&&&&&&&&&&

************************

y' = ln(2)(5)(2^(5t-1))

&&&&&&&&&&&&&&&&&&&&&&&&

************************

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aThis function is a composite. The inner function is g(x)=5t-1 and the outer function is f(z)

=2^z.

f'(z)=ln(2) * 2^z.

g ' (x)=5

so

(f(g(t)) ' = g ' (t)f ' (g(t))=

5 ln(2) * 2^(5t-1).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `q**** Query 3.4.67 was 3.4.68 (3d edition 3.4.56) y = k (x), y ' (1) = 2.

What is the derivative of k(2x) when x = 1/2?

What is the derivative of k(x+1) when x = 0?

{]What is the derivative of k(x/4) when x = 4?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

&&&&&&&&&&&&&&&&&&&&&&&&

************************

(k(2x))' = 2k'(2x)

(k(2x))'(.5) = 2k'(1) = 2(2) = 4

(k(x+1))' = (1)k'(x+1)

(k(x+1))'(0) = k'(0+1) = 2

(k(x/4))'= 1/4(k'(x/4))

(k(x/4))'(4) = 1/4(k'(4/4)) = (1/4)(2) = .5

&&&&&&&&&&&&&&&&&&&&&&&&

************************

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** We apply the Chain Rule:

( k(2x) ) ' = (2x) ' * k'(2x) = 2 k(2x).

When x = 1/2 we have 2x = 1.

k ' (1) = y ' (1) = 2 so

when x = 1/2

( k(2x) ) ' = 2 k(2 * 1/2) = 2 * k'(1) = 2 * 2 = 4.

(k(x+1)) ' = (x+1)' k ' (x+1) = k ' (x+1) so

when x = 0 we have

(k(x+1) ) ' = k ' (x+1) = k ' (1) = 2

(k(x/4)) ' = (x/4)' k'(x/4) = 1/4 * k'(x/4) so when x = 4 we have

(k(x/4))' = 1/4 * k'(x/4) = 1/4 k'(4/4) = 1/4 * 2 = 1/2. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `qQuery 3.4.81 (3d edition 3.4.68). Q = Q0 e^(-t/(RC)). I = dQ/dt.

Show that Q(t) and I(t) both have the same time constant.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

&&&&&&&&&&&&&&&&&&&&&&&&

************************

dQ/dt = (Q0)(-1/RC)e^(-t/(RC))

both have the same time constant.

&&&&&&&&&&&&&&&&&&&&&&&&

************************

confidence rating #$&*:OK

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** We use the Chain Rule.

(e^(-t/(RC)))' = (-t/(RC))' * e^(-t/(RC)) = -1/(RC) * e^(-t/(RC)).

So dQ/dt = -Q0/(RC) * e^(-t/(RC)).

Both functions are equal to a constant factor multiplied by e^(-t/(RC)).

The time constant for both functions is therefore identical, and equal to RC. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `qQuery problem 3.5.5 (unchanged since 3d edition) (formerly 4.5.6). What is the

derivative of sin(3x)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

&&&&&&&&&&&&&&&&&&&&&&&&

************************

y = sin(3x)

y' = (3)cos(3x)

&&&&&&&&&&&&&&&&&&&&&&&&

************************

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** sin(3x) is the composite of g(x) = 3x, which is the 'inner' function (the first function

that operates on the variable x) and the 'outer' function f(z) = sin(z).

Thus f(g(x)) = sin(g(x)) = sin(3x).

The derivative is (f (g(x) ) ' = g ' (x) * f' ( g(x) ).

g ' (x) = (3x) ' = 3 * x ' = 3 ', and

f ' (z) = (sin(z) ) ' = cos(z).

So the derivative is [ sin(3x) ] ' = ( f(g(x) ) ' = g ' (x) * f ' (g(x) ) = 3 * cos(3x). **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `qQuery problem 3.5.50 was 3.5.48 (3d edition 3.5.50) (formerly 4.5.36). Give the

equations of the tangent lines to graph of y = sin(x) at x = 0 and at `pi/3

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

&&&&&&&&&&&&&&&&&&&&&&&&

************************

y = sin(x)

y' = cos(x)

y'(0) = cos(0) = 1

y(0) = 0

so 0 = 0(1) + b

b = 0

y = x

y'(pi/3) = .5

y(pi/3) = sqrt(3)/2

sqrt(3)/2 = .5(pi/3) + b

b =~ .3424

y = .5x + .3424

&&&&&&&&&&&&&&&&&&&&&&&&

************************

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a** At x = 0 we have y = 0 and y ' = cos(0) = 1.

The tangent line is therefore the line with slope 1 through (0,0), so the line is y - 0 = 1 ( x -

0) or just y = x.

At x = `pi/3 we have y = sin(`pi/3) = `sqrt(3) / 2 and y ' = cos(`pi/3) = .5.

Thus the tangent line has slope .5 and passes thru (`pi/3,`sqrt(3)/2), so its equation is

y - `sqrt(3)/2 = .5 (x - `pi/3)

y = .5 x - `pi/6 + `sqrt(3)/2. Approximating:

y - .87 = .5 x - .52. So

y = .5 x + .25, approx.

Our approximation to sin(`pi/6), based on the first tangent line:

The first tangent line is y = x. So the approximation at x = `pi / 6 is

y = `pi / 6 = 3.14 / 6 = .52, approximately.

Our approximation to sin(`pi/6), based on the second tangent line, is:

y = .5 * .52 + .34 = .60.

`pi/6 is equidistant from x=0 and x=`pi/3, so we might expect the accuracy to be the same

whichever point we use.

The actual value of sin(`pi/6) is .5. The approximation based on the tangent line at x = 0 is

.52, which is much closer to .5 than the .60 based on the tangent line at x = `pi/3.

The reason for this isn't too difficult to see. The slope is changing more quickly around x =

`pi/3 than around x = 0. Thus the tangent line will move more rapidly away from the actual

function near x = `pi/3 than near x = 0. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `qQuery 3.5.34 (3d edition 3.5.40). Der of sin(sin x + cos x)

What is the derivative of the given function and how did you find it?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

&&&&&&&&&&&&&&&&&&&&&&&&

************************

y = sin(sin(x) + cos(x))

y' = (cos(x) - sin(x))(cos(sin(x) + cos(x)))

take the derivative of whatever is within sine and multiply it by cosine (the derivative) of

whatever was within sine: ex. sin(2x) = 2cos(2x) or (sin(z))' = z'cos(z)

&&&&&&&&&&&&&&&&&&&&&&&&

************************

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aThe function y = sin( sin(x) + cos(x) ) is the composite of g(x) = sin(x) + cos(x) and f(z) =

sin(z).

The derivative of the composite is g ' (x) * f ' (g(x) ).

g ' (x) = (sin(x) + cos(x) ) ' = cos(x) - sin(x).

f ' (z) = sin(z) ' = cos(z).

So g ' (x) * f ' (g(x)) = ( cos(x) - sin(x) ) * cos( sin(x) + cos(x) ).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

&#This looks very good. Let me know if you have any questions. &#